Dampak Penggunaan Geget Terhadap Psikologi Anak Remaja - Heni Maria (Institut Agama Kristen Negeri Kupang, 2022)
The variety of existing information and applications is the result of the rapid and increasingly sophisticated development of information technology, which makes it easier for people to access information and facilitate communication. In addition, the benefits and sophistication of gadgets cannot be separated from the opinions of its users. Gadget is one of the variables that can affect the way young adults behave, because climate, family and guardian variables also play an important role in the lives of adolescents. Therefore, the purpose of this research is to find out how gadgets affect the psychology of adolescents. Qualitative approach and descriptive method are used in this research. Through observation and interviews, the authors were able to gather impact information in using gadget technology. Therefore, it is expected that parents will always supervise how their children use gadgets, limit their use, and be able to overcome changes in attitudes that occur in adolescents so that deviant behavior does not occur.